2021
DOI: 10.3991/ijim.v15i19.23773
|View full text |Cite
|
Sign up to set email alerts
|

GeoGebra Integration in Elementary Initial Teacher Training: The Case of 3-D Shapes

Abstract: <p class="0abstract">The integration of technology in learning is increasingly popular and inevitable, especially during the Covid-19 pandemic. In mathematics education, Geogebra has been used as a pedagogical tool in learning mathematics from elementary to university. The present study aims to explore first-year prospective elementary teachers’ experience constructing 3-D shapes using GeoGebra. This study uses a case study method with 40 first-year prospective elementary teachers from an elementary init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…This conclusion backs up the findings of [37], which explains that social cognitive learning theory can be implemented in the online learning process during the Covid-19 epidemic. This finding is consistent with the previous study [20], [24], [26], [29], [31], [64], which found that GeoGebra can be integrated into mathematics learning and aid in the process of grasping mathematical ideas. On the other hand, the results of the study report that the problem-based learning model is not bad.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This conclusion backs up the findings of [37], which explains that social cognitive learning theory can be implemented in the online learning process during the Covid-19 epidemic. This finding is consistent with the previous study [20], [24], [26], [29], [31], [64], which found that GeoGebra can be integrated into mathematics learning and aid in the process of grasping mathematical ideas. On the other hand, the results of the study report that the problem-based learning model is not bad.…”
Section: Discussionsupporting
confidence: 93%
“…Equations and coordinates, on the other hand, may be directly inserted. Algebraically specified functions can therefore be dynamically adjusted [20], [34]- [36].…”
Section: Geogebramentioning
confidence: 99%
See 3 more Smart Citations